Modelowanie katastrof w ustalaniu poziomu retencji dla wybranych typów umów reasekuracyjnych - Poprawska, Ewa (Catastrophe risk modelling for calculating level of retention in selected types of reinsurance contracts, 2006)
Insurance risk models differ depending on the purpose that they are created, but in case of catastrophic losses, there are some common difficulties. The main one is lack of historical data. Catastrophic events seldom occurs, that is why insurers cannot build models based on historical data. Moreover the available data not are always appropriate for analysing current or future situation. That is why different solutions are applied. The aim of the paper is to describe the way of modeling catastrophic losses and using them to obtain the level of retention in selected types of reinsurance contracts.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 392-400